Health locus of control, self-efficacy and dispositional optimism in patients with diabetes mellitus 2 - review of the literature - Krzemińska, Sylwia; Bąk, Ewelina (Journal of Education, Health and Sport, 2023)
In the literature on prevention, health promotion and psychology, much attention is paid to the determinants of health, with particular emphasis on lifestyle and practiced health behaviors [1]. The individual choice of the type of behavior adopted depends on the patient’s level of general knowledge, in particular knowledge of health care, as well as experience, motivation, recognized values ​​and set goals. An important element of considerations on this subject is to recognize the beliefs and motives of patients’ actions in the area of ​​life that significantly affects health [2]. An important factor modifying activity in the process of maintaining biopsycho-social health or preventing complications of an existing chronic disease is the locus of health control and the sense of self-efficacy, as well as a sense of optimism in life. The paper analyzes selected psychological resources, health locus of control, self-efficacy and a sense of optimism in patients with type 2 diabetes, which are related to the process of coping with a chronic disease. A chronic disease confronts the patient with many tasks and challenges that change over time. They depend, among others on: type of disease, method of treatment, cognitive characteristics of the sick person, emotional and behavioral reaction as well as socio-cultural conditions in which the person functions. [3]